Cardioprotective and antioxidant effects of Bougainvillea glabra against isoproterenol induced myocardial necrosis in albino rats - Rakam Gopi Krishna; Raja Sundara Rajan (International Journal of Phytomedicine, 2018)
The present study was executed to evaluate the myocardial protective effect of methanol extract of Bougainvillea glabra against isoproterenol induced myocardial necrosis in rats. Myocardial necrosis was induced by subcutaneous injection of isoproterenol (85mg/kg body weight) on 29th and 30th day at an interval of 24 hours. Myocardial necrosis was evident from the changes of marker enzymes in serum, plasma and heart tissue. The activities of serum cardiac marker enzymes such as lactate dehydrogenase (LDH), creatine kinase myoglobin (CK-MB), serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), triglycerides (TG), total cholesterol (TC), high density lipoproteins (HDL), low density lipoproteins (LDL), very low density lipoproteins (VLDL) and total protein (TP) were estimated. In addition, plasma TBARS and plasma LDH levels were also recorded. Antioxidant parameters viz catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPx) and malondialdehyde (MDA) levels were performed in heart tissue homogenate. The outcome of the study indicated that, pretreatment with methanol extract of Bougainvillea glabra to isoproterenol induced rats significantly prevented the altered serum cardiac marker enzymes, plasma levels and antioxidant parameters to near normal status. The cardioprotective effect was compared with propranolol (10 mg/kg, oral) which was used as the standard. Histopathological findings exposed a reduced degree of necrosis and inflammation succeeding pretreatment with Bougainvillea glabra.Based on these results, it was suggested that methanol extract of Bougainvillea glabra prevents myocardial necrosis and oxidative stress induced by isoproterenol.